Passive Protection Elements Breach Resistance Modeling - Ladislav Kittel; Tomas Lovecek (Communications - Scientific letters of the University of Zilina, 2011)
This article originated in response to requirement for creation of quantitative evaluation system of passive protection elements resistance, which could be implemented into complex process of technical effectiveness evaluation of property protection systems. It deals with design of model, which could be a basis for estimation of breach resistance time and which would use attributes of material of chosen homogeneous passive protection element – building construction. The article analyses possibilities of mathematical modeling of attack on homogeneous passive protection element on the basis of specifically chosen tool and attack method. The model used will simulate an attempt to overcome a wall made from single layer monolithic concrete panel using a hammer as chosen tool. For the purpose of attack modeling a model of contact force effect of direct central impact on passive protection element, while omitting the deformations on tool and the effect of deformation forces created by impact on the wall section will be studied. Subsequently the model will be applied to the breach resistance time assessment method based on the number of impacts required for overcoming of barrier.